University trademark: Suggestions for Vietnam’s Universities from the Experiencesin the United States and China - Ngoc Phuong Hong, Nguyen (VNU Journal of Science: Legal Studies; Vol 42 No 2, 2026)
Amid increasing global competition in higher education, university trademarks serve not only as legal protection but also as strategic assets for institutional identity, branding, and revenue generation. While their importance is widely recognized in many countries, especially in the United States and China, research and practice in Vietnam remain in their early stages. So far, branding strategies of Vietnamese universities still largely emphasize admissions and marketing, with comparatively limited focus on intellectual property governance and long-term institutional identity. To address this gap, this article employs doctrinal and comparative methods to i) define the concept and roles of university trademarks, ii) analyze challenges in their protection and commercialization, and iii) draw lessons from the experiences of the United States and China. By advancing this analysis, the paper contributes to academic and policy discussions on integrating trademark management into university governance and internationalization efforts, thereby safeguarding legal rights, enhancing institutional reputation, and increasing the competitiveness of Vietnam’s universities in the global higher education market.